Standardization of different doses and duration of plant derived smoke water on growth, yield and yield attributing traits of linseed (Linum usitatissimum L.): STANDARDIZATION OF PLANT DERIVED SMOKE WATER TREATMENT ON LINSEED - B LOHITHA; PRASHANT KUMAR RAI; SHIVAM KUMAR RAI (Journal of Oilseeds Research, 2024)
Harnessing the potential of smoke water treatments, derived from plant combustion, this study delves into their impact on various growth and physiological parameters of linseed plants. Through a randomized controlled trial featuring 13 treatments along with control, we meticulously evaluated different concentrations and durations of smoke water application. Linseed seeds were meticulously sown under controlled conditions, enabling the comprehensive assessment of field emergence, plant height, flowering duration, branching patterns, chlorophyll content, seed yield, oil content, and protein content. Notably, Treatment 2 (1% smoke water for 16 hours) emerged as a frontrunner, showcasing superior performance across multiple parameters, including accelerated growth, enhanced flowering, increased branching, improved chlorophyll content, and higher seed yield and oil content. These findings underscore the promising role of smoke water as an environmentally sustainable and effective agricultural intervention to augment crop productivity and quality in linseed cultivation. Further research endeavors are warranted to delve deeper into the underlying mechanisms and refine application protocols, thereby unlocking the full potential of smoke water treatments in modern agricultural practices.